2022
DOI: 10.1097/sla.0000000000005472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gender-affirming Facial Feminization Surgery on Psychosocial Outcomes

Abstract: Objective: This study investigates the effect of gender-affirming facial feminization surgery (FFS) on psychosocial outcomes in patients with gender dysphoria. Background: Comprehensive analyses of psychosocial outcomes after gender-affirming FFS are absent in the literature resulting in a paucity of information on the impact of FFS on quality of life as well as ramifications in health insurance coverage of FFS. Methods: Scores from 11 validated, quantitative instruments from the Patient-Reported Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…A total of 17 380 records were identified from the search, with 286 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 380 records were identified from the search, with 286 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ...…”
Section: Resultsmentioning
confidence: 99%
“…This differed from the findings of Caprini et al, which showed positive effects in social relations through improvements in social isolation after FFS. 5…”
Section: Discussionmentioning
confidence: 99%
“…7 FFS has been shown to improve mental health outcomes, with transgender patients reporting significantly reduced rates of anxiety, depression, anger, and social isolation. 5 Although FFS plays an important role in gender-affirmation, there remains limited accuracy and heterogenous methods of reporting the quality of surgical outcomes related to patient satisfaction of facial appearance. 8,9 The FACE-Q instrument is a validated patient-reported outcome measure (PROM) that has become increasingly widespread in clinical and research practices to assess facial outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Such care has been shown to be related to improved mental health, decreased suicidal thoughts, and improved quality of life. [9][10][11][12][13][14] Thus, gender-affirming care is a life-saving and life-changing treatment.…”
mentioning
confidence: 99%